Government Programs for Disabled Children: A Practitioner's Guide to Policy and Programs in Florida - LeaAnne DeRigne (University of North Florida, 2016)
There are many government programs and benefits available to disabled children in the United States and include income-support programs, educational and therapeutic programs, and health services. This paper provides a practice/policy update for practitioners working with disabled children and their families. Doctors, nurses, counselors, and educators need to understand the rights of disabled children and their families. A short case scenario is presented followed by a summary of the federal and state policies that are available. Finally, sources of funding for each program are presented.